COMPARATIVE STUDY OF 1% TERBINAFINE WITH 1% CLOTRIMAZOLE IN THE MANAGEMENT OF LOCALIZED TINEA CORPORIS AND TINEA CRURIS INFECTION - V.L.M.RAMAN M.D (International Journal of Pharma and Bio Sciences, 2014)
The dermatophytosis constitutes a group of superficial fungal infections that infect only superficial keratinized tissues viz. stratum corneum of epidermis, hairs and nails. The infection is commonly designated as ringworm or Tinea. Tinea corporis and Tinea cruris are the clinical forms of dermatophytosis or ringworm infection or Tinea infection. Pruritis is the most common symptom. Typical lesion is usually annular or polycyclic and has a well marginated raised border, composed of multiple erythematous papulovesicles or scales with a clear center Out of 30 patients of Terbinafine group 27 patients have effective treatment in terms of both clinical improvement and mycological cure (i.e., KOH negativity and culture negativity) at the end of 1st week. Out of 30 patients in Clotrimazole group 26 patients have effective treatment in terms of both clinical improvement and mycological cure. (i.e., KOH negativity and culture negativity) at the end of 4th week. The results of the present study suggest that 1 week of 1% Terbinafine applied twice daily is more effective than 4 weeks of 1% Clotrimazole cream applied twice daily. Thus 1% Terbinafine provides rapid relief of symptoms and short duration of therapy for tinea cruris and corporis infections.